Pembelajaran Luar Kelas Berbasis Pemecahan Masalah untuk Meningkatkan Motivasi Belajar Mahasiswa - Karuru, Perdy (Jurnal Pengabdi, 2025)
Problem-solving-based out-of-class learning activities aim to increase students' learning motivation in Business English, Philosophy of Science, and Introduction to Business courses. This activity involves students and lecturers in the learning process outside the campus, such as in local companies, business communities, and other places relevant to the lecture material. Over the course of four months, students actively solve real problems faced by partners, such as barriers to business communication in English, ethical challenges in decision-making, and small business management strategies. The problem-solving approach is carried out through field observations, group discussions, interviews, and data analysis. Lecturers function as facilitators who help students connect theory with practice. The results of this activity showed an increase in students' motivation to learn, as seen from their enthusiasm in discussions, a deeper understanding of the course concepts, and their ability to provide innovative solutions. The program also provides tangible benefits to external partners through solutions implemented by students. This activity has proven to be an effective learning model in supporting the concept of Independent Learning Independent Campus.